Tekstualisasi Dan Kontekstualisasi Ajaran Islam (Sebuah Wacana Interrelasi Dalam Pemaknaan Al-NusUs Al-Syar’iyyah) - Budi Rahmat Hakim (Universitas Islam Negeri Alauddin, 2014)
Al-Quran was revealed down to Muhamamd saw. It consist of some chapters and verses written in Arabic language. Thus, it needs methods or approaches to understand the essential meaning. There are two approaches to understand the islamic text. The first, contextual approaches which is frequently applied by Liberal Islam. The second, textual approach which is usually applied by Fundamental Islam.